2005
DOI: 10.1063/1.1862784
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optical and structural properties of 1.3μm GaInNAs∕GaAs multiple quantum-well heterostructures with stepped strain-mediating layers

Abstract: Role of Sb in the growth and optical properties of 1.55 μ m Ga In N ( Sb ) As ∕ Ga N As quantum-well structures by molecular-beam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The suppression of the low-energy broadening and the decrease of the line width by about 30% when going from Sample A to Sample B confirm that a lower growth temperature and the incorporation of indium in the barrier material (Sample B only) have a positive effect on the optical quality of Ga 1−x In x N y As 1−y MQW structures. 6,9 We should note that apart from a low-energy broadening in Sample A, a high-energy feature is present in the PL signal of Sample B only. Very little is known up to now about its origin, but we have found that the feature does not exhibit a shift in energy as a function of either excitation power or temperature (not shown here), suggesting that it cannot be due to free-exciton recombination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The suppression of the low-energy broadening and the decrease of the line width by about 30% when going from Sample A to Sample B confirm that a lower growth temperature and the incorporation of indium in the barrier material (Sample B only) have a positive effect on the optical quality of Ga 1−x In x N y As 1−y MQW structures. 6,9 We should note that apart from a low-energy broadening in Sample A, a high-energy feature is present in the PL signal of Sample B only. Very little is known up to now about its origin, but we have found that the feature does not exhibit a shift in energy as a function of either excitation power or temperature (not shown here), suggesting that it cannot be due to free-exciton recombination.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of indium in the barrier material of Sample B reduces the strain at the QW-barrier interface, further lowering the inhomogeneity of the Ga 1−x In x N y As 1−y QWs in the sample. 6,9 Hence, the effect of carrier localization is expected to be much stronger in Sample A, while the period of the modulation is larger in Sample B. The result is that, in both samples, the electrons may be trapped by nitrogen-rich 24,31 regions, while the holes may only be localized in In-rich parts of the sample, separating them from electrons in the N-rich regions at low temperatures in an out-of-phase manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since invented in 1995 by Kondow et al [1], the GaInNAs / GaAs material system has been extensively studied as an alternative to InP-based optoelectronic devices operating in the 1.3 -1.5 µm wavelength range [2,3]. Despite difficulties related to crystal growth [2,3], the quest for the development of telecommunication grade GaInNAs-based lasers continues at an accelerated pace.…”
Section: Development Of Telecommunication Grade Gainnas Laser Diodesmentioning
confidence: 99%
“…Despite difficulties related to crystal growth [2,3], the quest for the development of telecommunication grade GaInNAs-based lasers continues at an accelerated pace. This development is powered by the growing demand for higher bandwidth in telecommunication networks [4].…”
Section: Development Of Telecommunication Grade Gainnas Laser Diodesmentioning
confidence: 99%